(untitled) (Italian Journal of Public Health, 2008)
Background: Sometimes referred to as ‘the demographic time bomb,’ the European Union, state and local governments are concerned about the impact of an ageing population on both sustainable economic development and the demand for health and social support services. Seeking to mitigate these pressures, the Organisation for Economic Co-operation and Development (OECD) has developed a policy framework Live Longer: Work Longer and the World Health Organization (WHO) has set a policy framework for Active Ageing which maintains that early life course interventions can reduce levels of disability and dependency in older age. The WHO European Healthy Cities Network (WHO-EHCN) promotes healthy urban planning to encourage healthy lifestyles and maintain older people as a resource in the workplace and to their communities. Our objective is to develop a new model dependency ratio (NMDR) for European cities which synthesises these three policy frameworks. Methods: Starting from the classic formulation of the dependency ratio (DR), which compares the ’dependent’ population segments with the working-age or ’productive’ segments, the model is developed in six stages, drawing on data from secondary European and national sources and from primary sources contained in Healthy Ageing Profiles of fifteen (WHO-EHCN) cities. Results: From an orthodox baseline, the second stage of modelling increases the DR by moving economically inactive people of working age from denominator to numerator. Thereafter, refinements introduced in stages three to six, gradually reduce the DR. Conclusions: The NMDR challenges the ’demographic time bomb’ predicted by orthodox formulations and can be used as a tool by city decision makers.